2005
DOI: 10.1017/s1431927605510407
|View full text |Cite
|
Sign up to set email alerts
|

Progress and Perspectives for Atomic-Resolution Electron Microscopy

Abstract: The atomic-resolution capabilities of the electron microscope, which first became widely accessible in the 1980s, have had a major impact across many disciplines [1]. With carefully prepared samples and correct operating conditions, assisted by quantitative image recording and processing, image characteristics can be interpreted directly in terms of individual atomic columns. With improvements in hardware and special attention to microscope environment, resolving powers close to or exceeding the one Ångstrom (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the very same year, it was also demonstrated that two diffracted beams could be passed simultaneously through the microscope objective lens to form interference fringes, or lattice fringes, the first representative image of a crystal lattice. Over the years the resolution gradually improved and the contrast mechanisms became well understood, for reviews of these developments, see Smith (1997Smith ( , 2008. Correlating the image to atomic positions is not always simple since the relative phases of the diffracted beams depend on the thickness and microscope focus and aberrations, so the imaging of dislocation core structures relied on extensive image simulations, at least until the recent introduction of aberration correctors (Kisielowski et al 2006).…”
Section: Direct Imaging Of Dislocation Core Structuresmentioning
confidence: 99%
“…In the very same year, it was also demonstrated that two diffracted beams could be passed simultaneously through the microscope objective lens to form interference fringes, or lattice fringes, the first representative image of a crystal lattice. Over the years the resolution gradually improved and the contrast mechanisms became well understood, for reviews of these developments, see Smith (1997Smith ( , 2008. Correlating the image to atomic positions is not always simple since the relative phases of the diffracted beams depend on the thickness and microscope focus and aberrations, so the imaging of dislocation core structures relied on extensive image simulations, at least until the recent introduction of aberration correctors (Kisielowski et al 2006).…”
Section: Direct Imaging Of Dislocation Core Structuresmentioning
confidence: 99%